Bannermen tales (zidishu) : Manchu storytelling and cultural hybridity in the Qing dynasty - Chiu, Elena Suet-Ying, 1974- (Harvard-Yenching Institute monograph series, 2018)
"The first full-length study in English of zidishu, an important storytelling and performance genre rooted in the hybrid, popular culture of Qing dynasty Beijing, which was associated with the culture of the Qing bannermen--the Manchu's military and administrative personnel. Argues that zidishu employed cultural hybridization as a way of performing and thereby perpetuating Manchu identity"--